Repeated injections of D-Amphetamine evoke rapid and dynamic changes in phase synchrony between the prefrontal cortex and hippocampus - AHN, SUNGWOO; Linsenbardt, David N.; Lapish, Christopher C.; Rubchinsky, Leonid L. (Frontiers in Behavioral Neuroscience, 2013)
Repeated drug use evokes a number of persistent alterations in oscillatory power and synchrony. How synchronous activity in cortico-hippocampal circuits is progressively modified with repeated drug exposure, however, remains to be characterized. Drugs of abuse induce both short-term and long-term adaptations in cortical and hippocampal circuits and these changes are likely important for the expression of the altered behavioral and neurobiological phenotype associated with addiction. The present study explores how the initial (up to one hour) pharmacological response to D-Amphetamine (AMPH) is altered with repeated injections in the rat. The methods employed herein allow for the progressive changes in synchronized dynamics with repeated intermittent AMPH exposure to be characterized over short time scales (minutes). Specifically, we examined the temporal variations of phase-locking strength in delta and theta bands within the prefrontal cortex (PFC) and between PFC and hippocampus (HC) shortly after drug injection. After the first injection of AMPH synchrony increased within the PFC in the delta band, which was followed, by an increase in theta synchrony between the PFC and HC several minutes later. This relationship switched after repeated AMPH injections, where increases in theta synchrony between the PFC and HC preceded increases in delta synchrony in the PFC. The time-course of increases in synchronous activity were negatively correlated between the PFC delta and the PFC-HC theta. Collectively these data highlight the potential role of PFC-HC circuits in the development of addiction and outline dynamic changes in the time-course that cortico-hippocampal circuits become synchronized with repeated AMPH exposure.